Cross-sectional associations between cortical thickness and physical activity in older adults with spontaneous memory complaints: The MAPT Study - Jérémy Raffin; Yves Rolland; Clara Fischer; Jean-François Mangin; Audrey Gabelle; Bruno Vellas; Philipe de Souto Barreto (Elsevier, 2023)
Background: Age-related changes in brain structure may constitute the starting point for cerebral function alteration. Physical activity (PA) demonstrated favorable associations with total brain volume, but its relationship with cortical thickness (CT) remains unclear. We investigated the cross-sectional associations between PA level and CT in community-dwelling people aged 70 years and older. Methods: A total of 403 older adults aged 74.8 ± 4.0 years (mean ± SD) who underwent a baseline magnetic resonance imaging examination and who had data on PA and confounders were included. PA was assessed with a questionnaire. Participants were categorized according to PA levels. Multiple linear regressions were used to compare the brain CT (mm) of the inactive group (no PA at all) with 6 active groups (growing PA levels) in 34 regions of interest. Results: Compared with inactive persons, people who achieved PA at a level of 1500−1999 metabolic equivalent task-min/week (i.e., about 6−7 h of brisk walking for exercise and those who achieved it at 2000−2999 metabolic equivalent task-min/week (i.e., 8−11 h of brisk walking for exercise) had higher CT in the fusiform gyrus and the temporal pole. Additionally, dose−response associations between PA and CT were found in the fusiform gyrus (B = 0.011, SE = 0.004, adj. p = 0.035), the temporal pole (B = 0.026, SE = 0.009, adj. p = 0.048), and the caudal middle frontal gyrus, the entorhinal, medial orbitofrontal, lateral occipital, and insular cortices. Conclusion: This study demonstrates a positive association between PA level and CT in temporal areas such as the fusiform gyrus, a brain region often associated to Alzheimer's disease in people aged 70 years and older. Future investigations focusing on PA type may help to fulfil remaining knowledge gaps in this field.